Internet and distributed computing knowledge in today’s world - Pathan, Al-Sakib Khan (IJIDCS Press, Dhaka, Bangladesh, 2011)
Editor-in-Chief's foreword for International Journal on Internet and Distributed Computing Systems (IJIDCS)